The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13093126
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Benefits of Curcumin on Female Reproductive Disorders: A Review

Abstract: Curcumin is one of the main polyphenolic compounds in the turmeric rhizome. It possesses antioxidant, anti-inflammatory, anti-cancer, anti-arthritis, anti-asthmatic, anti-microbial, anti-viral and anti-fungal properties. This review aims to provide an overview of the potential health benefits of curcumin to treat female reproductive disorders, including polycystic ovary syndrome (PCOS), ovarian failure and endometriosis. Comprehensive information on curcumin was retrieved from electronic databases, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…[41] Previous studies show reduced organ index weight of thymus and spleen post-treatment with curcumin and piperine. [42][43] All the treatment groups were a significant change in reducing the organ weight index of the thymus and spleen. Histopathology studies showed changes in tissue associated with the disease.…”
Section: Discussionmentioning
confidence: 96%
“…[41] Previous studies show reduced organ index weight of thymus and spleen post-treatment with curcumin and piperine. [42][43] All the treatment groups were a significant change in reducing the organ weight index of the thymus and spleen. Histopathology studies showed changes in tissue associated with the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Animal studies have shown how cucurmin can have a therapeutic potential against endometriosis by decreasing certain cytokines and having antiangiogenic effects. 40,41 The benefits of turmeric that patients with endometriosis see are not well described in the literature. While effects have not been well studied there are no harmful side effects seen with turmeric supplementation.…”
Section: Turmericmentioning
confidence: 99%
“…Curcuma longa L.-Curcumin Curcumin is a yellow pigment and an active component of the rhizome of Curcuma longa L., or turmeric [167]. It is known to possess antioxidant, anti-inflammatory, anti-cancer, anti-arthritis, anti-asthmatic, antimicrobial, antiviral and antifungal properties [167,168]. Considering that curcumin is a powerful antioxidant natural compound, it may represent another potential treatment to alleviate oxidative stress in glaucoma.…”
Section: Crocus Sativus L-crocetin and Crocinmentioning
confidence: 99%